2009
DOI: 10.1249/mss.0b013e3181a518f0
|View full text |Cite
|
Sign up to set email alerts
|

Protease Supplementation Improves Muscle Function after Eccentric Exercise

Abstract: Protease supplementation seems to attenuate muscle strength losses after eccentric exercise by regulating leukocyte activity and inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(36 citation statements)
references
References 36 publications
2
33
1
Order By: Relevance
“…However, the TBARS values for the African American group and the Caucasian group were very similar at all time-points. Second, diet was not controlled leading up to the study, but we felt it was not necessary because recent research has shown that in subjects of similar age and health to those in the present study, the day to day differences in macronutrient ingestion are very minimal (2,7). Finally, most exercise studies use more aggressive exercise intensities, and the use of a submaximal exercise test in this study may not replicate the oxidative stress responses to other maximal or exhaustive exercises.…”
Section: Discussionmentioning
confidence: 97%
“…However, the TBARS values for the African American group and the Caucasian group were very similar at all time-points. Second, diet was not controlled leading up to the study, but we felt it was not necessary because recent research has shown that in subjects of similar age and health to those in the present study, the day to day differences in macronutrient ingestion are very minimal (2,7). Finally, most exercise studies use more aggressive exercise intensities, and the use of a submaximal exercise test in this study may not replicate the oxidative stress responses to other maximal or exhaustive exercises.…”
Section: Discussionmentioning
confidence: 97%
“…The most investigated lipid mediator in human models of exerciseinduced muscle injury has been PGE 2 , likely because of its proinflammatory and hyperalgesic properties and their hypothesized association with sympotomology of DOMs. Although some studies have reported elevated circulating PGE 2 concurrent with the onset of DOMs 24 -72 h following exerciseinduced muscle injury (95,102), others have found no such response (4,9,13,23,24,41). The reasons for this are unclear but may be related to differences in the intensity of skeletal muscle loading [for example, downhill running (13) vs. resistance exercise (95,102)] and/or the volume of active muscle mass [unilateral/isolation (4,9,23,24,41) vs. bilateral/compound exercises (95,102)].…”
Section: Discussionmentioning
confidence: 99%
“…The limited studies available have focused on the potential role of select COX-1 and COX-2 pathway-derived proinflammatory/hyperalgesic PGs (e.g., PGE 2 ) in underlying the symptoms of exercise-induced muscle injury, which occur Ն24 h into recovery. While some studies have reported elevated circulating levels PGE 2 , concurrent with the onset of delayed onset muscle soreness (DOMs) 24 -72 h postexercise (95,102), others have found no such response (4,9,13,23,24,41). Additionally, a large body of research on the use of NSAIDs, the main therapeutic mechanism of action of which is thought to be blockade of the COX-1 and COX-2 pathways to relieve symptoms of DOMs, has yielded conflicting and inconclusive results (reviewed in Ref.…”
mentioning
confidence: 99%
“…Specific protease supplementation protocols accelerated muscle recovery after strenuous exercises (Miller et al, 2004; Beck et al, 2007; Buford et al, 2009). These findings may indicate that protein digestibility was improved; however, the reported studies lacked direct measurements of protein digestibility.…”
Section: Enzyme and Hormone Supplementation And Use Of Hydrolysates mentioning
confidence: 99%